Continuous Flow Polymer Synthesis toward Reproducible Large‐Scale Production for Efficient Bulk Heterojunction Organic Solar Cells. Issue 19 (21st August 2015) - Pirotte, Geert; Kesters, Jurgen; Verstappen, Pieter; Govaerts, Sanne; Manca, Jean; Lutsen, Laurence; Vanderzande, Dirk; Maes, Wouter
Abstract Organic photovoltaics (OPV) have attracted great interest as a solar cell technology with appealing mechanical, aesthetical, and economies‐of‐scale features. To drive OPV toward economic viability, low‐cost, large‐scale module production has to be realized in combination with increased top‐quality material availability and minimal batch‐to‐batch variation. To this extent, continuous flow chemistry can serve as a powerful tool. In this contribution, a flow protocol is optimized for the high performance benzodithiophene–thienopyrroledione copolymer PBDTTPD and the material quality is probed through systematic solar‐cell evaluation. A stepwise approach is adopted to turn the batch process into a reproducible and scalable continuous flow procedure. Solar cell devices fabricated using the obtained polymer batches deliver an average power conversion efficiency of 7.2 %. Upon incorporation of an ionic polythiophene‐based cathodic interlayer, the photovoltaic performance could be enhanced to a maximum efficiency of 9.1 %.